Journeys of the learning soul: Plato to Descartes - Hugo, Wayne (Rhodes University, Faculty of Education, Department of Education, 2004)
This thesis aims to build up a picture of what it has meant for us within the western canon to educate a human being through the depths and heights of existence. It uses narrative accounts of educational journeys from ancient, medieval and early modern sources to develop an integral picture of the spectrum of education along with the techniques and fore-structures needed to guide a student through the various stages and encounters. Key metaphors, journeys and relationships - Diotirna's ladder of beauty, Plato's cave, Philo's Abraham and Sarah, Origen's bride and Bridegroom, Plotinus' journey of the alone to the Alone, Augustine's Confessions, the tragic love of Abelard and Heloise, Dante's encounters in the infernal, purgatorial and paradisical realms of human experience, Shakespeare's great playing within the same realm, and Descartes' doubting genius provide a rich ensemble, each resonating with the next, opening out intellectual, affective, volitional, and imaginative paths through the full terrain of human existence. This multidimensional approach points towards a flexible and insightful pedagogics that works with the enormous variety and capacity of human learning rather than heavy-handedly insisting on one path, or, even worse, not recognizing and dealing with specific areas of human living that occur in the upper and lower reaches of our educational endeavours. Phenomenological, Hermeneutic and Integral methods suggested by Heidegger and Wilber amongst others were used to inform the process of research. The results of this thesis are not contained in its reconunendations but in the effects of its reading. It is itself a tool that embodies and encourages the principles of an educational tradition that has existed within the history of western learning, not seeking a return to ancient or medieval ways but to provide a backlight that assists current initiatives working with the full range of human potential.
Keywords: Education -- Philosophy; Education -- History; Education, Ancient; Education, Greek